Silicon-carbon composite material as well as preparation method and application thereof

By adding inert flow-gliding microspheres in the preparation process of silicon-based negative electrode materials, the problems of uneven particle deposition and coating and aggregation are solved, and uniform fluidization and efficient preparation of silicon-carbon composite materials are achieved, which improves electrochemical performance and reduces production costs.

CN119797330APending Publication Date: 2025-04-11SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510046646.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art has defects in the preparation process of silicon-based negative electrode materials such as uneven particle deposition and coating, particle aggregation, and cumbersome production processes and high cost.

Method used

By adding inert gas flow microspheres to the reaction material, the auxiliary material is fluidized, preventing the generation of bubbles and grooves when gas passes through the particle layer, and achieving uniform fluidization of micron-scale material particles.

Benefits of technology

The uniform fluidization and deposition of silicon-carbon composite materials is achieved, the preparation process flow is shortened, gas consumption is saved, electrochemical performance is improved, and production costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797330A_ABST
    Figure CN119797330A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-carbon composite material as well as a preparation method and application thereof. The preparation method of the silicon-carbon composite material comprises the following steps: in inert gas, performing chemical vapor deposition on a mixture A in a fluidized state and silicon source gas; the mixture A comprises a carbon-based material and inert flow-aiding microspheres; the degree of sphericity of the inert flow-aiding microspheres is 0.9-1; the particle size of the inert flow-aiding microspheres is 30 [mu] m-150 [mu] m; the mass ratio of the carbon-based material to the inert flow-aiding microspheres is (0.1-5): 1. According to the preparation method of the silicon-carbon composite material, the inert flow-aiding microspheres are added into the reaction materials, the auxiliary materials are fluidized, bubbles and channeling are prevented from being generated when gas passes through a particle layer, uniform fluidization of micron-sized material particles is achieved, the technological process for preparing the silicon-carbon composite material is shortened, and the production cost is reduced. The gas consumption in the reaction process is reduced, the electrochemical performance of the silicon-carbon composite material is improved, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon composite material and a preparation method and application thereof. Background Art

[0002] At present, the preparation of silicon-based negative electrode materials mainly relies on rotary kiln technology. This technology promotes the movement of particles in the furnace by rotating the furnace body, and cracks the gas source gas under high temperature conditions under the protection of inert gas to achieve silicon element deposition or conductive carbon material coating. However, due to the morphology and process limitations of the airflow pulverized particles, the material particles are prone to sticking to the wall and agglomeration in the rotary kiln, resulting in uneven gas-solid mixing, which in turn affects the material performance.

[0003] In comparison, the gas-solid fluidized coating technology uses gas to suspend particles, reduce the contact and adhesion between material particles, achieve uniform and efficient gas-solid mixing, have good mass transfer capabilities, and can achieve uniform deposition and coating on the surface and inside of the granular material. As the negative electrode material of the battery, the particle size of the material must be less than 30μm. In actual production and processing, the too small particle size requirement leads to an increase in weak mutual forces such as friction and van der Waals force between particles, which makes it easy for particles to agglomerate. After the gas is introduced, cavitation, channel flow, and slug flow are easily formed, making it difficult to form a stable and uniform fluidized state. Some similar research results, such as Chinese patents CN105006559A and CN113991090A, all use adhesives to assemble the original powder of silicon-based negative electrode materials into spherical secondary particles with larger particle sizes, and then add the secondary particles to the fluidized bed for fluidized carbon deposition and coating. After the CVD treatment is completed, the particles are cleaved and broken to the size of the original particles. The whole process is cumbersome and time-consuming. The production process adds multiple processing steps, which seriously increases the production cost. It is also time-consuming and labor-intensive and may affect the integrity of the deposition and coating layers, thereby affecting the actual performance of the material and reducing the service life of the material in lithium batteries. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defects of uneven particle deposition and coating, particle agglomeration, cumbersome production process and high cost in the preparation process of silicon-based negative electrode materials in the prior art, and provide a silicon-carbon composite material and its preparation method and application. The preparation method of the silicon-carbon composite material of the present invention adds inert flow-aiding microspheres to the reaction materials to assist the fluidization of the materials, prevent the generation of bubbles and channel flow when the gas passes through the particle layer, realize the uniform fluidization of micron-sized material particles, shorten the process flow of preparing the silicon-carbon composite material, save gas consumption in the reaction process, improve the electrochemical performance of the silicon-carbon composite material, and reduce the production cost.

[0005] The present invention solves the above technical problems through the following technical solutions:

[0006] The present invention provides a method for preparing a silicon-carbon composite material, which comprises the following steps:

[0007] In an inert gas, the mixture A in a fluidized state is subjected to chemical vapor deposition with a silicon source gas;

[0008] The mixture A comprises a carbon-based material and inert flow-aiding microspheres;

[0009] The sphericity of the inert flow-aiding microspheres is 0.9-1;

[0010] The particle size of the inert flow-aiding microspheres is 30 μm-150 μm;

[0011] The mass ratio of the carbon-based material to the inert flow-aiding microspheres is (0.1-5):1.

[0012] Preferably, the carbon-based material is a combination of one or more of porous carbon, carbon black, natural graphite, artificial graphite, mesocarbon microbeads, carbon nanotubes, carbon fibers and graphene, such as porous carbon.

[0013] In this scheme, the selection of the type of carbon-based material can optimize the conductivity and structural stability of the material, and help improve the electrochemical performance of silicon-carbon composite materials, especially in terms of cycle performance and rate performance.

[0014] Preferably, the particle size of the carbon-based material is 0.4 μm-30 μm, more preferably 1.5 μm-28.5 μm, for example 20 μm.

[0015] In this solution, the particle size of the carbon-based material is 0.4μm-30μm, which helps to improve the reaction efficiency of the carbon-based material and the silicon source gas, while enhancing the stability of the material, reducing particle agglomeration, and is beneficial to the uniformity of the fluidization process and the uniformity of vapor deposition.

[0016] Preferably, the inert flow-aiding microspheres are a combination of one or more of alumina, zirconia or silica.

[0017] Preferably, the particle size of the inert flow-aiding microspheres is 90 μm.

[0018] Preferably, the inert flow-aiding microspheres have a sphericity of 0.95-1, such as 0.97.

[0019] Preferably, the mass ratio of the carbon-based material to the inert flow-aiding microspheres is (0.67-4):1, and more preferably (0.67-1):1.

[0020] Preferably, the inert gas is a combination of one or more of argon, helium or nitrogen.

[0021] Preferably, the silicon source gas is a combination of one or more of monosilane, disilane, dichlorosilane or trichlorosilane.

[0022] Preferably, during the chemical vapor deposition reaction process, the volume ratio of the inert gas to the silicon source gas is (1-4):1.

[0023] Preferably, during the chemical vapor deposition reaction process, the flow rate of the inert gas is 4 L / min-8 L / min.

[0024] Preferably, during the chemical vapor deposition reaction process, the flow rate of the silicon source gas is 2 L / min-4 L / min.

[0025] Preferably, during the chemical vapor deposition reaction process, the total gas velocity of the inert gas and the silicon source gas is 0.03 m / s-0.1 m / s.

[0026] Preferably, the reaction temperature of the chemical vapor deposition is 300-600°C, more preferably 400°C-500°C.

[0027] Preferably, the reaction time of the chemical vapor deposition is 10 min-400 min, more preferably 60 min-180 min.

[0028] More preferably, the inert gas is nitrogen.

[0029] More preferably, the silicon source gas is monosilane.

[0030] Further preferably, during the chemical vapor deposition reaction process, the volume ratio of the inert gas to the silicon source gas is 2:1.

[0031] Further preferably, during the chemical vapor deposition reaction process, the flow rate of the inert gas is 6 L / min.

[0032] Further preferably, during the chemical vapor deposition reaction process, the flow rate of the silicon source gas is 3 L / min.

[0033] Further preferably, during the chemical vapor deposition reaction process, the total gas velocity of the inert gas and the silicon source gas is 0.05 m / s.

[0034] More preferably, the reaction temperature of the chemical vapor deposition is 450°C.

[0035] More preferably, the reaction time of the chemical vapor deposition is 70 min-160 min, for example 70 min-90 min.

[0036] Preferably, the mixture A is prepared by mixing the carbon-based material and the inert flow-aiding microspheres.

[0037] More preferably, the mixing is performed in a mixer.

[0038] More preferably, the mixing frequency is 10-40 Hz, and even more preferably 25-35 Hz, such as 30 Hz.

[0039] More preferably, the mixing time is 0.5h-3h.

[0040] Preferably, the method of making the mixture A in a fluidized state is:

[0041] In an inert gas, place mixture A in a fluidized bed reactor and heat it.

[0042] In this solution, the carbon-based material and the inert flow-aiding microspheres are mixed, and in a fluidized bed reactor, the good fluidized motion state of the inert flow-aiding microspheres in the reactor is utilized to improve the full movement of the material and avoid adhesion and agglomeration.

[0043] More preferably, the inert gas is a combination of one or more of argon, helium or nitrogen, such as nitrogen.

[0044] More preferably, the terminal temperature of the heating is 400°C-500°C, for example 450°C.

[0045] More preferably, the heating rate from room temperature to the terminal temperature of the heating is 5°C / min-15°C / min, for example, 10°C / min.

[0046] Preferably, after the chemical vapor deposition step, a carbon coating step is also included.

[0047] In this scheme, the core-shell structure formed by carbon coating can improve the conductivity of the active material while alleviating the problem of particle breakage and pulverization caused by volume change during lithium insertion and extraction, thereby improving the battery's rate and cycle performance.

[0048] Further preferably, the heating rate from the reaction temperature of the chemical vapor deposition to the reaction temperature of the carbon coating is 3° C. / min-10° C. / min, for example 5° C. / min.

[0049] More preferably, the reaction temperature of the carbon coating is 400°C-700°C, for example 600°C.

[0050] More preferably, the reaction time of the carbon coating is 10 min-400 min, more preferably 30 min-90 min.

[0051] Further preferably, the carbon source used for the carbon coating is a hydrocarbon mixture, more preferably a combination of one or more of methane, ethane, propane, isopropane, butane, isobutane, ethylene, propylene, acetylene, butene and natural gas, such as acetylene.

[0052] More preferably, the flow rate of the carbon source used for the carbon coating is 1 L / min-4 L / min, for example, 2 L / min.

[0053] More preferably, the carbon coating atmosphere is an inert atmosphere, and more preferably the inert atmosphere is a combination of one or more of nitrogen, argon and helium, such as nitrogen.

[0054] Preferably, after the chemical vapor deposition step, a screening step is also included.

[0055] In this scheme, the inert flow-aiding microspheres can be separated by screening treatment to obtain the silicon-carbon composite material, and the inert flow-aiding microspheres can be reused after being separated.

[0056] More preferably, the mesh size of the sieve used in the screening process is 200-400 mesh.

[0057] Further preferably, the screening equipment is a vibration screening equipment or an ultrasonic screening equipment.

[0058] Further preferably, after the screening process, the particle size of the silicon-carbon composite material is 0.40 μm-30 μm.

[0059] The present invention also provides a silicon-carbon composite material, which is prepared by the preparation method of the silicon-carbon composite material as described above.

[0060] Preferably, the silicon content of the silicon-carbon composite material is 35 wt%-56 wt%, for example, 48.8 wt%, 49.2 wt% or 49.4 wt%.

[0061] The present invention also provides an application of the silicon-carbon composite material as described above in the preparation of battery pole pieces.

[0062] The positive and progressive effects of the present invention are:

[0063] (1) Improved fluidization stability and uniformity: The present invention can effectively enhance the fluidization stability during the reaction by adding inert flow-aiding microspheres to the reaction materials, avoiding the generation of bubbles and channeling, thereby achieving uniform fluidization of micron-sized material particles. This improvement improves the uniformity of subsequent deposition and coating processes.

[0064] (2) Reuse of inert flow-aiding microspheres reduces production costs: The inert flow-aiding microspheres used in the present invention have the advantage of being reusable. After being mixed with raw materials, they can be used multiple times in the production process, thereby effectively reducing production costs and improving resource utilization efficiency.

[0065] (3) Reduce carrier gas consumption and improve production efficiency: The addition of inert flow-aiding microspheres in the present invention helps to reduce the amount of carrier gas required, while improving the stability and efficiency of the reaction process. This method not only saves gas consumption and reduces production costs, but also significantly improves production efficiency and ensures efficient preparation of silicon-carbon composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 This is the XRD diagram of the silicon-carbon composite material of Example 1.

[0067] Figure 2 This is the SEM image of the silicon-carbon composite material of Example 1.

[0068] Figure 3 This is the particle size test distribution result of Example 1.

[0069] Figure 4 This is the particle size test distribution result of Comparative Example 2.

[0070] Figure 5 This is the BSE backscattering scanning image of Comparative Example 1.

[0071] Figure 6 This is the BSE backscatter scanning image of Example 1. DETAILED DESCRIPTION

[0072] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples.

[0073] In the following examples, the porous carbon particles are from China Steel Ma'anshan Mining Institute New Materials Technology Co., Ltd., with a model of CH 20 and a particle size of 20 μm.

[0074] In the following embodiments, the mixer is from Suzhou Songtai Instrument Equipment Co., Ltd., and the model is SYH-30 three-dimensional motion mixer.

[0075] In the following examples, the fluidized bed reactor is from Suzhou Neutral Nanotechnology Co., Ltd., model FB CVD-20.

[0076] In the following examples, the silica microspheres are from Suzhou Zhiyi Microsphere Technology Co., Ltd., model KBsphere-90Si, with a particle size of 90 μm and a sphericity of 0.97.

[0077] In the following examples, the vibration screening equipment is from Xinxiang Gaofu Machinery Co., Ltd., model number is S49-AC-200.

[0078] In the following examples, the white carbon black powder is from Shandong Kasong Chemical Co., Ltd., model KS-630, particle size D50 is 5.7 μm, and particle sphericity is less than 0.2.

[0079] Example 1

[0080] 300g of porous carbon particles and 300g of silica microspheres were mixed evenly in a mixer. The mixing time was 30min, the mixing frequency of the equipment was 30Hz, and the mixture was put into a fluidized bed reactor. Nitrogen was introduced as a protective gas, and the temperature was raised to 450°C at a rate of 10°C / min. After the temperature was constant, a mixture of monosilane and nitrogen was introduced, wherein the volume ratio of monosilane to nitrogen was 1:2, the flow rate of monosilane was 3L / min, the flow rate of nitrogen was 6L / min, and the total gas velocity of the reaction process was controlled to be 0.05m / s for silicon deposition. After 90min, the introduction of monosilane was stopped, the temperature was raised to 600°C at 5°C / min, acetylene gas was introduced at 2L / min, and it was closed after maintaining for 30min, and naturally cooled to room temperature under an inert atmosphere. The obtained product was sieved by a vibrating sieving device to obtain a silicon-carbon composite material with a particle size of 0.40μm-30μm.

[0081] Example 2

[0082] 240g of porous carbon particles and 360g of silica microspheres were mixed evenly in a mixer. The mixing time was 30min, the mixing frequency of the equipment was 30Hz, and the mixture was put into a fluidized bed reactor. Nitrogen was introduced as a protective gas, and the temperature was raised to 450°C at a rate of 10°C / min. After the temperature was constant, a mixture of monosilane and nitrogen was introduced, wherein the volume ratio of monosilane to nitrogen was 1:2, the flow rate of monosilane was 3L / min, the flow rate of nitrogen was 6L / min, and the total gas velocity of the reaction process was controlled to be 0.05m / s for silicon deposition. After 70min, the introduction of monosilane was stopped, the temperature was raised to 600°C at 5°C / min, acetylene gas was introduced at 2L / min, and it was closed after maintaining for 30min, and naturally cooled to room temperature under an inert atmosphere. The obtained product was sieved by a vibrating sieving device to obtain a silicon-carbon composite material with a particle size of 0.40μm-30μm.

[0083] Example 3

[0084] 360g of porous carbon particles and 240g of silica microspheres were mixed evenly in a mixer. The mixing time was 30min, the mixing frequency of the equipment was 30Hz, and the mixture was put into a fluidized bed reactor. Nitrogen was introduced as a protective gas, and the temperature was raised to 450°C at a rate of 10°C / min. After the temperature was constant, a mixture of monosilane and nitrogen was introduced, wherein the volume ratio of monosilane to nitrogen was 1:2, the flow rate of monosilane was 3L / min, the flow rate of nitrogen was 6L / min, and the total gas velocity of the reaction process was controlled to be 0.05m / s for silicon deposition. After 110min, the introduction of monosilane was stopped, the temperature was raised to 600°C at 5°C / min, acetylene gas was introduced at 2L / min, and it was closed after maintaining for 30min, and naturally cooled to room temperature under an inert atmosphere. The obtained product was sieved by a vibrating sieving device to obtain a silicon-carbon composite material with a particle size of 0.40μm-30μm.

[0085] Example 4

[0086] 480g of porous carbon particles and 120g of silica microspheres were mixed evenly in a mixer. The mixing time was 30min, the mixing frequency of the equipment was 30Hz, and the mixture was put into a fluidized bed reactor. Nitrogen was introduced as a protective gas, and the temperature was raised to 450°C at a rate of 10°C / min. After the temperature was constant, a mixture of monosilane and nitrogen was introduced, wherein the volume ratio of monosilane to nitrogen was 1:2, the flow rate of monosilane was 3L / min, the flow rate of nitrogen was 6L / min, and the total gas velocity of the reaction process was controlled to be 0.05m / s for silicon deposition. After 144min, the introduction of monosilane was stopped, the temperature was raised to 600°C at 5°C / min, acetylene gas was introduced at 2L / min, and it was closed after maintaining for 30min, and naturally cooled to room temperature under an inert atmosphere. The obtained product was sieved by a vibration screening device to obtain a silicon-carbon composite material with a particle size of 0.40μm-30μm.

[0087] Comparative Example 1

[0088] 300g of porous carbon particles were put into a fluidized bed reactor, nitrogen was introduced as a protective gas, and the temperature was raised to 450°C at a rate of 10°C / min. After the temperature was constant, a mixture of monosilane and nitrogen was introduced, wherein the volume ratio of monosilane to nitrogen was 1:2, silane was 3L / min, and nitrogen was 6L / min. The total gas velocity of the reaction process was controlled to be 0.05m / s, and silicon deposition was performed. After 90min, the introduction of monosilane was stopped, the temperature was raised to 600°C at 5°C / min, acetylene gas was introduced at 2L / min, maintained for 30min, and then closed, and naturally cooled to room temperature under an inert atmosphere. The obtained product was sieved by a vibrating screening device to obtain a silicon-carbon composite material with a particle size of 0.40μm-30μm.

[0089] Comparative Example 2

[0090] 300g of porous carbon particles and 300g of white carbon black powder are mixed evenly in a mixer. The mixing time is 30min, the mixing frequency of the equipment is 30Hz, and it is put into a fluidized bed reactor. Nitrogen is introduced as a protective gas, and the temperature is raised to 450°C at a rate of 10°C / min. After the temperature is constant, a mixture of monosilane and nitrogen is introduced, wherein the volume ratio of monosilane: nitrogen is 1:2, the flow rate of monosilane is 3L / min, the flow rate of nitrogen is 6L / min, and the total gas velocity of the reaction process is controlled to be 0.05m / s, and silicon deposition is performed. After 90min, the introduction of monosilane is stopped, the temperature is raised to 600°C at 5°C / min, acetylene gas is introduced at 2L / min, and it is closed after maintaining for 30min, and naturally cooled to room temperature under an inert atmosphere. The obtained product is sieved by a vibrating screening device to obtain a silicon-carbon composite material with a particle size of 0.40μm-30μm.

[0091] Comparative Example 3

[0092] 514g of porous carbon particles and 86g of silica microspheres were mixed evenly in a mixer. The mixing time was 30min, the mixing frequency of the equipment was 30Hz, and the mixture was put into a fluidized bed reactor. Nitrogen was introduced as a protective gas, and the temperature was raised to 450°C at a rate of 10°C / min. After the temperature was constant, a mixture of monosilane and nitrogen was introduced, wherein the volume ratio of monosilane to nitrogen was 1:2, the flow rate of monosilane was 3L / min, the flow rate of nitrogen was 6L / min, and the total gas velocity of the reaction process was controlled to be 0.05m / s for silicon deposition. After 154min, the introduction of monosilane was stopped, the temperature was raised to 600°C at 5°C / min, acetylene gas was introduced at 2L / min, and it was closed after maintaining for 30min, and naturally cooled to room temperature under an inert atmosphere. The obtained product was sieved by a vibrating sieving device to obtain a silicon-carbon composite material with a particle size of 0.40μm-30μm.

[0093] Comparative Example 4

[0094] 533g of porous carbon particles and 67g of silica microspheres were mixed evenly in a mixer. The mixing time was 30min, the mixing frequency of the equipment was 30Hz, and the mixture was put into a fluidized bed reactor. Nitrogen was introduced as a protective gas, and the temperature was raised to 450°C at a rate of 10°C / min. After the temperature was constant, a mixture of monosilane and nitrogen was introduced, wherein the volume ratio of monosilane to nitrogen was 1:2, the flow rate of monosilane was 3L / min, the flow rate of nitrogen was 6L / min, and the total gas velocity of the reaction process was controlled to be 0.05m / s for silicon deposition. After 160min, the introduction of monosilane was stopped, the temperature was raised to 600°C at 5°C / min, acetylene gas was introduced at 2L / min, and it was closed after maintaining for 30min, and naturally cooled to room temperature under an inert atmosphere. The obtained product was sieved by a vibrating sieving device to obtain a silicon-carbon composite material with a particle size of 0.40μm-30μm.

[0095] Effect Example: Button Battery Performance Test

[0096] (1) XRD test

[0097] The full spectrum test of the silicon-carbon composite material of Example 1 was carried out using a Shimadzu XRD-6100 device with a scanning speed of 5°C / min. Figure 1 As shown, the crystalline silicon element in the silicon-carbon composite material has four relatively obvious characteristic peaks, among which the strongest characteristic peak is located at about 28.44 degrees, and there is no obvious characteristic peak at 24-32 degrees, indicating that there is no crystalline silicon in the sample, and the silicon element is distributed in an amorphous state in the carbon-based material of the silicon-carbon composite material.

[0098] (2) SEM test

[0099] Figure 2 This is a SEM desktop scanning electron microscope image (Phenom Pharos G2) of Example 1. The test method is to take an appropriate amount of the silicon-carbon composite material of Example 1 and evenly sprinkle it on the conductive backing adhesive, place it on the sample table, and test it. Three images are taken at each of the magnifications of 500 / 1000 / 3000 / 5000. Figure 2 Taking a SEM desktop scanning electron microscope image at a magnification of 1000, it was observed that the silicon-carbon composite material of Example 1 had no agglomeration or adhesion, and the overall particles had a structure with a coating layer on the surface.

[0100] (3) Electrochemical performance test

[0101] The silicon-carbon composite material obtained in Examples 1-4 and Comparative Examples 1-4 was used to prepare the negative electrode material of lithium-ion batteries, and button batteries were prepared according to the following method: a binder, a conductive agent and a solvent were added to the silicon-carbon composite material, stirred and slurried, coated on a copper foil, and dried and rolled to obtain a negative electrode sheet; the binder used was LA132, the conductive agent was SP, and the solvent was NMP, wherein the amount ratio of the silicon-carbon composite material, SP, LA132, and NMP was 95g: 1g: 4g: 220mL; the electrolyte was LiPF6 solution (the solvent was a mixed solution of EC and DEC with a volume ratio of 1: 1, and the concentration of LiPF6 was 1mol / L), the metal lithium sheet was the counter electrode, and the diaphragm was a polypropylene film. The button battery was assembled in an argon-filled glove box, and the electrochemical performance was carried out on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.005V~2.0V and a charge and discharge rate of 0.1C. Three groups of electrochemical performance tests were performed on each experimental sample.

[0102] The test results of Examples 1-4 and Comparative Examples 1-4 are shown in Table 1 below.

[0103] Table 1 Electrochemical performance test results of examples and comparative examples

[0104]

[0105] As can be seen from the table, in the experimental test results of the embodiments, the electrochemical test performance of embodiments 1 and 2 is better than that of embodiment 3, indicating that the mass ratio of the carbon-based material and the inert flow-aiding microspheres has a significant effect on the deposition and coating results, and the mass ratio affects the deposition and coating uniformity of the sample. When the mass ratio is small, the relative uniformity is better, and the deposition effect decreases as the mass ratio increases. The test results of the embodiments and the comparative examples show that the results of embodiments 1-4 are better than the results shown in comparative examples 1-4, which indicates that in the process of chemical vapor deposition, adding inert flow-aiding microspheres of specific particle size, sphericity and mass can effectively improve the fluidization state of the material and enhance the uniformity of vapor deposition.

[0106] (4) Particle size test

[0107] Take 2g of each silicon-carbon composite material of Example 1 and Comparative Example 2, add 10ml of pure water respectively, prepare slurry, after ultrasonication for 30s, select pure water test background, transfer 5ml of test solution into Malvern 3000 (Mastersizer3000+Pro) laser particle size analyzer sample test cell, and test. The test results of Example 1 are as follows: Figure 3 The test results of comparative example 2 are as follows Figure 4 It can be seen that in Comparative Example 2, white carbon black with a smaller particle size and worse sphericity was used for the auxiliary fluidization experiment. The experimental results showed that the sample was agglomerated, and the particle size test results showed that agglomeration and adhesion occurred, and the effect was significantly worse than the test results of Example 1.

[0108] (5) BSE backscatter scanning test

[0109] Backscatter imaging test method: Using a desktop scanning electron microscope (Phenom Pharos G2), take an appropriate amount of the silicon-carbon composite material of Example 1 and Comparative Example 1 and evenly sprinkle it on the conductive backing adhesive, place it on the sample table, and test it. Take 3 pictures at each of the magnifications of 500 / 1000 / 3000 / 5000. Figure 5 , Figure 6 The image analysis results show that according to the backscattered electron imaging principle and energy spectrum analysis (backscattered imaging can provide information on the microstructure and chemical composition of the sample. Elements with larger atomic numbers have larger scattering areas and appear brighter grayscale in backscattered electron imaging; the working principle of energy spectrum analysis is based on the energy scattering phenomenon of X-rays. By measuring the wavelength of these X-rays, the presence and content of each element in the sample can be determined, and then different element distributions can be presented in the image). It can be seen that the green main body in the figure is the imaging result of the silicon element, and the dark red area is the imaging result of the carbon element. Figure 5 The distribution of silicon, carbon and oxygen elements in the sample energy spectrum analysis. Figure 5In the comparative example 1 shown, the silicon and carbon elements shown in green and red, respectively, are unevenly distributed, and the carbon element accounts for a high proportion in some particles; Figure 6 The figure shows the distribution of silicon, carbon and oxygen in the sample. Figure 6 The red carbon element in the sample particles is mostly the carbon element detected in the background conductive glue. Figure 5 Compared with the comparative example 1, the sample of Example 1 shows that the silicon element is evenly distributed and the deposition effect is better than that of the comparative example 1.

[0110] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A method for preparing a silicon-carbon composite material, characterized in that: It includes the following steps: In an inert gas, the mixture A in a fluidized state is subjected to chemical vapor deposition with a silicon source gas; The mixture A comprises a carbon-based material and inert flow-aiding microspheres; The sphericity of the inert flow-aiding microspheres is 0.9-1; The particle size of the inert flow-aiding microspheres is 30 μm-150 μm; The mass ratio of the carbon-based material to the inert flow-aiding microspheres is (0.1-5):

1.

2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The carbon-based material is a combination of one or more of porous carbon, carbon black, natural graphite, artificial graphite, mesophase carbon microspheres, carbon nanotubes, carbon fibers and graphene, such as porous carbon; and / or, the particle size of the carbon-based material is 0.4 μm-30 μm, preferably 1.5 μm-28.5 μm, for example 20 μm; And / or, the inert flow-aiding microspheres are a combination of one or more of alumina, zirconium oxide or silicon dioxide; And / or, the particle size of the inert flow-aiding microspheres is 90 μm; and / or, the inert flow-aiding microspheres have a sphericity of 0.95-1, for example 0.97; And / or, the mass ratio of the carbon-based material to the inert flow-aiding microspheres is (0.67-4):1, preferably (0.67-1):

1.

3. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The inert gas is a combination of one or more of argon, helium or nitrogen; And / or, the silicon source gas is a combination of one or more of monosilane, disilane, dichlorosilane or trichlorosilane; And / or, during the chemical vapor deposition reaction, the volume ratio of the inert gas to the silicon source gas is (1-4): 1; And / or, during the chemical vapor deposition reaction process, the flow rate of the inert gas is 4L / min-8L / min; And / or, during the chemical vapor deposition reaction process, the flow rate of the silicon source gas is 2L / min-4L / min; And / or, during the chemical vapor deposition reaction process, the total gas velocity of the inert gas and the silicon source gas is 0.03 m / s-0.1 m / s; And / or, the reaction temperature of the chemical vapor deposition is 300-600° C., preferably 400° C.-500° C.; And / or, the reaction time of the chemical vapor deposition is 10 min-400 min, preferably 60 min-180 min.

4. The method for preparing the silicon-carbon composite material according to claim 3, characterized in that: The inert gas is nitrogen; And / or, the silicon source gas is monosilane; And / or, during the chemical vapor deposition reaction process, the volume ratio of the inert gas to the silicon source gas is 2:1; And / or, during the chemical vapor deposition reaction process, the flow rate of the inert gas is 6 L / min; And / or, during the chemical vapor deposition reaction process, the flow rate of the silicon source gas is 3 L / min; And / or, during the chemical vapor deposition reaction process, the total gas velocity of the inert gas and the silicon source gas is 0.05 m / s; And / or, the reaction temperature of the chemical vapor deposition is 450° C.; And / or, the reaction time of the chemical vapor deposition is 70 min-160 min, for example, 70 min-90 min.

5. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The preparation method of the mixture A is to mix the carbon-based material and the inert flow-aiding microspheres; Preferably, the mixing is carried out in a mixer; Preferably, the mixing frequency is 10-40 Hz, preferably 25-35 Hz, for example 30 Hz; Preferably, the mixing time is 0.5h-3h.

6. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method of making the mixture A in a fluidized state is: In an inert gas, place the mixture A in a fluidized bed reactor and heat it up; Preferably, the inert gas is a combination of one or more of argon, helium or nitrogen, such as nitrogen; Preferably, the end temperature of the heating is 400°C-500°C, for example 450°C; Preferably, the heating rate from room temperature to the terminal temperature of the heating is 5°C / min-15°C / min, for example, 10°C / min.

7. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: After the chemical vapor deposition step, a carbon coating step is also included; Preferably, the heating rate from the reaction temperature of the chemical vapor deposition to the reaction temperature of the carbon coating is 3°C / min-10°C / min, for example 5°C / min; Preferably, the reaction temperature of the carbon coating is 400°C-700°C, for example 600°C; Preferably, the carbon coating reaction time is 10 min-400 min, more preferably 30-90 min; Preferably, the carbon source used for the carbon coating is a hydrocarbon mixture, more preferably a combination of one or more of methane, ethane, propane, isopropane, butane, isobutane, ethylene, propylene, acetylene, butene and natural gas, such as acetylene; Preferably, the flow rate of the carbon source used for the carbon coating is 1 L / min-4 L / min, for example, 2 L / min; Preferably, the carbon coating atmosphere is an inert atmosphere, and more preferably the inert atmosphere is a combination of one or more of nitrogen, argon and helium, such as nitrogen.

8. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: After the chemical vapor deposition step, a screening step is also included; Preferably, the mesh size of the sieve used in the screening process is 200-400 mesh; Preferably, the screening equipment is a vibration screening equipment or an ultrasonic screening equipment; Preferably, after the screening process, the particle size of the silicon-carbon composite material is 0.40 μm-30 μm.

9. A silicon-carbon composite material, characterized in that: It is prepared by the preparation method of the silicon-carbon composite material according to any one of claims 1 to 8; Preferably, the silicon content of the silicon-carbon composite material is 35 wt%-56 wt%, for example, 48.8 wt%, 49.2 wt% or 49.4 wt%.

10. Use of the silicon-carbon composite material as claimed in claim 9 in preparing battery pole pieces.

Citation Information

Patent Citations

  • Preparation method of silicon-carbon composite material

    CN112133915A

  • Processes and systems for using silica particles in fluid bed reactor

    CN112469499A

  • Aromatization fluidized bed composite catalyst and application thereof

    CN112691694A

  • Method of depositing silicon on carbon materials and forming an anode for use in lithium ion batteries

    US20080261116A1